2011
DOI: 10.1016/j.jbtep.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Reducing contamination by exposure plus safety behaviour

Abstract: The use of hygienic wipes, the safety behaviour used in this experiment, did not preclude significant reductions in contamination, disgust, fear and danger. If it is replicated and extended over a longer time-frame, this finding may enable practitioners to enhance the acceptability of cognitive behavioural treatments and boost their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 20 publications
10
71
0
Order By: Relevance
“…This type of therapy can be very challenging for patients, with many of them unable to complete or engage in ERP, which has led to the idea of modifying ERP to allow for certain safety behaviors (11). Therefore, it remains a critical question how the processing of safety could be altered in OCD.…”
supporting
confidence: 91%
“…This type of therapy can be very challenging for patients, with many of them unable to complete or engage in ERP, which has led to the idea of modifying ERP to allow for certain safety behaviors (11). Therefore, it remains a critical question how the processing of safety could be altered in OCD.…”
supporting
confidence: 91%
“…Repeated exposure to a threat-relevant stimulus (e.g., a dirty bed-pan) has been shown to reduce subject fear ratings, but not ratings of subjective disgust in students high on contamination fears (Olatunji, Wolitzky-Taylor, Willems, Lohr, & Armstrong, 2009). In cases where exposure results in fear and disgust reductions, disgust responses may be more likely to return, suggesting that the changes occurring in extinction are more ephemeral for disgust responses (Rachman, Shafran, Radomsky, & Zysk, 2011). This resilience of disgust responses may be most pronounced in individuals with C-OCD.…”
Section: Exposurementioning
confidence: 99%
“…Contextual and temporal factors influence the degree to which patients will be able to recall the new nonthreat associations when obsessional thoughts and external cues are encountered. It is as if the learning and memory system 3 A recent study suggested that the judicious use of safety behaviors may not be harmful to exposure therapy outcomes in OCD (Rachman, Shafran, Radomsky, & Zysk, 2011), yet the finding was limited to shortterm outcomes in a nonclinical undergraduate sample. Thus, our recommendation to eliminate safety behaviors and cues as much as possible still holds at present.…”
Section: Enhancing the Retrievability Of Nonthreat Associationsmentioning
confidence: 99%